Optimization of HALO structure effects in 45nm p-type MOSFETs device using Taguchi method - Fauziyah, Salehuddin; Ahmad, Ibrahim; Azlee Hamid, Fazrena; Zaharim, Azami; Elgomati, Husam Ahmed; Majlis, Burhanuddin Yeop; Apte, Prakash R. (International Journal of Engineering and Applied Sciences, 2011)
In this study, the Taguchi method was used to optimize the effect of HALO structure or halo implant variations on threshold voltage (VTH) and leakage current (ILeak) in 45nm p-type Metal Oxide Semiconductor Field Effect Transistors (MOSFETs) device. Besides halo implant dose, the other process parameters which used were Source/Drain (S/D) implant dose, oxide growth temperature and silicide anneal temperature. This work was done using TCAD simulator, consisting of a process simulator, ATHENA and device simulator, ATLAS. These two simulators were combined with Taguchi method to aid in design and optimize the process parameters. In this research, the most effective process parameters with respect to VTH and ILeak are halo implant dose (40%) and S/D implant dose (52%) respectively. Whereas the second ranking factor affecting VTH and ILeak are oxide growth temperature (32%) and halo implant dose (34%) respectively. The results show that after optimizations approaches is -0.157V at ILeak=0.195mA/μm.